2015
DOI: 10.1007/s10815-015-0541-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced blastocyst formation in reduced culture volume

Abstract: Purpose The aim of this prospective sibling oocyte study was to evaluate whether reduced culture volume improves blastocyst formation. Methods Twenty-three patients with extended embryo culture until day 5 were selected for the study. After injection, 345 sibling oocytes were individually cultured in either 25 or 7 μl droplets of Origio cleavage medium under oil. On day 3 of development, embryos were transferred to droplets with the corresponding volume of Origio blastocyst culture medium. Fertilization and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Secondary endpoint was the total number of good quality Day 3 embryos between cycles. EQ was classified similar to what is described in a previous study performed by De Munck et al ( 6 ), with a minor update in the classification (good quality embryos included up to <50% fragmentation).…”
Section: Methodsmentioning
confidence: 99%
“…Secondary endpoint was the total number of good quality Day 3 embryos between cycles. EQ was classified similar to what is described in a previous study performed by De Munck et al ( 6 ), with a minor update in the classification (good quality embryos included up to <50% fragmentation).…”
Section: Methodsmentioning
confidence: 99%
“…Embryo density during single embryo culture can have a dramatic effect on cell numbers, as well as cleavage, blastocyst and hatching rates in the mouse (Lane and Gardner, 1992;Melin et al, 2009;O'Neill, 1997;Paria and Dey, 1990). In humans, one study observed no effect of embryo density on blastocyst rate (Rijnders and Jansen, 1999), but evidence from two recent studies show that embryo density is an important factor in human blastocyst development, although their conclusions on optimal density were inconsistent (De Munck et al, 2015;Minasi et al, 2015). The beneficial effect of increasing embryo density may be explained by the concentration of autocrine factors in the media.…”
Section: Introductionmentioning
confidence: 99%
“…One study found no effect of altering the media volume from day 3 to 5; 205 however, a more recent study found that reducing the media volume for the entire duration of culture resulted in a higher blastocyst rate, 211 and yet another study reported the reverse, that is reduced media volume resulted in a lower blastocyst rate. 212 These contradictory results are probably because optimum embryo density is dependent on other culture conditions, including oxygen, 97,198,199,[213][214][215] which suggests that individual clinics will need to optimize embryo density for their culture system.…”
Section: Embryo Densitymentioning
confidence: 99%